First, we have to find the rate of change of the given function using the slope formula
![m=(y_2-y_1)/(x_2-x_1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/78uaqhwt0aws3qfwxigaftpihnmb1gzxtp.png)
Let's replace the points (0, 3) and (1, 0), where
![\begin{gathered} x_1=0 \\ x_2=1 \\ y_1=3 \\ y_2=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rwmqe1adtak1e74k5npjnez9kubr599f05.png)
![m=(0-3)/(1-0)=-3](https://img.qammunity.org/2023/formulas/mathematics/college/l53yjgc3vgcpmwzyi6cjsc6k6zg0pwp1w2.png)
The given function has a rate of change of -3.
Let's find the relationship with a lesser rate of change.
We can deduct that function C has a lesser rate because its rate is -6 which is less than -3.
Hence, the answer is C.